The Involvement of Preservice Teachers in Delivering of Sport Education - Akhmad Olih Solihin; Agi Ginanjar; Ali Budiman (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Competence of a teacher should have been obtained when studying in college. However, college students or preservice teachers feel lack of competence during their study in college. It is important for colleges to provide a learning experience for students to have competence in teaching before they become a teacher. Sport Education (SE) has its own uniqueness because in its implementation, it can directly include several learning models as a provision to teach students when becoming a teacher. The purpose of this study was to determine the enjoyment of students using SE based on the characteristics of SE, increased skills and understanding of sports, and the pleasure of using SE. This research uses survey type of descriptive methods. Participants of this study are 35 college students who will finish their studies in the eastern part of West Java province. The instrument of this study used the Sport Education Season Survey. Data analyzing techniques employed in this study were descriptive statistics and paired samples t-test. The results of the study stated that college students enjoyed the use of SE based on the characteristics of SE, that college students have increased skills and understanding of sports, and that college students preferred SE compared to conventional learning. Further investigation related to college students teaching skills in the use of SE needs to be conducted.